2007
DOI: 10.1080/00365520701405579
|View full text |Cite
|
Sign up to set email alerts
|

Systematic expression profiling of the gastric H+/K+ATPase in human tissue

Abstract: We therefore conclude that the only organ in humans expressing significant levels of the P-CAB target gastric H+/K+ ATPase is the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…Moreover, it has recently been reported that the only organ in humans expressing significant levels of the P-CAB target gastric H ϩ ,K ϩ -ATPase is the stomach (Herrmann et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has recently been reported that the only organ in humans expressing significant levels of the P-CAB target gastric H ϩ ,K ϩ -ATPase is the stomach (Herrmann et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The REU unit describes the expression of a target RNA relative to the 18S rRNA internal standard of the respective sample (Herrmann et al, 2007).…”
Section: Real-time Quantitative Pcr (Taqman)mentioning
confidence: 99%
“…The effects induced are the same as observed by longterm PPI-use. Gastric H þ /K found in bone [Herrmann et al, 2007]. However, there are in vitro experiments suggesting that the PPI omeprazole decreases bone resorption [Tuukkanen and Vaananen, 1986] possibly through inhibition of the osteoclastic vacuolar H þ /K þ ATPase [Mizunashi et al, 1993].…”
mentioning
confidence: 95%